The orientation and determination of drainage corridor in the lower Tra Khuc river - Ve river - Hung, Hoa Manh; Huong, Nguyen Thi Thao; Hang, Phan Thi Thanh; Anh, Tran Thi Ngoc; Quy, Nguyen Ba; Linh, Tran Manh (Vietnam Journal of Earth Sciences, 2014)
Applicating forms of hydrology in shaping and determining drainage corridor in the lower Tra Khuc river, Ve river by avoiding flood, reducing flood and adaptating to flood is reasonable, scientific and practical in flood disaster situation increasingly complicated and climate change when the city of Quang Ngai expansion overlooking the sea in the future. Restoring and expanding network of river bed for Phu Vinh river, Diem Dien river - Kinh Giang river, the river network Bau Giang - Ong Trong - Phu Tho and the river Cai Bua. Served drainage flooding and flooding in low-topography downstream of Tra Khuc river, Ve river when the rain, the storm is essential.Marine motivation factors (waves, currents and tides along the coast,...) play a major role in narrowing the (filled) river mouth Cua Dai (Tra Khuc river) and Cua Lo (Ve river). The momentum factor river (river flood flow,...) are factors and motivation to extend and help to maintain river mouth bed. To stabilize the river bed width, should the building of a breakwater, to prevent the sand on either side of the mouth river.